Recortes biográficos das taieiras de Lagarto-SE - Santana, André Barbosa de (2023)
The objective is to investigate the development and resistance of cultural relations and popular cultures of Taieiras in Lagarto, Sergipe. In order to achieve the proposed objectives and central discussions of this research, I based myself on studies by theorists such as Dosse (2015), Canclini (2013), Arfush (2010), Dantas (2013) and Manetta (2021), among others. Therefore, this dissertation is characterized as an explanatory study, therefore, with a qualitative approach, having as a methodological study the research of the (auto) biographical method. From the recomposition of my memory and experiences with the Taieiras, as well as the oral and biographical reports of the members of this dance group, the intention is to apprehend in their cultural dynamics, from the origin and hierarchies, passing through productions, processes of social interaction in the community, to resistance over the years, recreating itself, reinventing itself and contributing to its existence.